Purificação e caracterização de uma ß-glucuroniodase extraída do molusco Mesogastropoda Ampularidae Pomacea sp - Andrade, Maria Lúcia Lira de (2006)
This work studies the involved enzymatic way in the metabolism of glycosaminoglycans sulfateds in the mollusc Pomacea sp. Had been identified endoglycosidases and exoglycosidases in the enzymatic extract of the mollusc Pomacea sp by means of hydrolysis activity in condroitim sulphate of whale cartilage and of the p-Nitrofenil-β-glucuronide, respectively. The enzymatic extracts qere obtained of Pomacea sp. being used of 0.1 sodium acetate buffer, pH 5.0 and later centrifugated the 8,000 x g and the presents proteins in the sobrenadante were submitted to the fractionament with two crescents ammonium sulphate concentrations, the visualized activity biggest in the F2 fraction (50-80%). The β-glucuronidase (F3) was isolated in gel chromatography filtration Biogel 1.5m, the purification degree was ratified in Chromatography Liquid of high efficiency (HPLC). The enzyme was purificated 6.362,5 times with 35,6% yield. The β -glucuronidase isolated in this work showed a molecular mass of 100 kDa, determined for eletroforese in poliacrilamida gel . The determination of the ideal kinetic parameters for the catalysis of the p-nitrofenil- β -glucuronide for β-glucuronidase, showed excellent activity in pH 5,0 and temperature 65ºC for 6 hours and apparent Km of 72 x 10-2 mM. It is necessary for the total degradation of 3mM of p-N-β-glucoronide, the amount of 1,2μg of ss-glucuronidase. The BaCl2 increased the activity of ss-glucuronidase, and the activity was inhibited completely by the composites SDS and NaH2PO4